Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

If we define the affine function as

$f(\lambda x + (1-\lambda)y) = \lambda f(x) + (1-\lambda)f(y)$ for every $x,y \in R^d$ and $\lambda \in R$

How to show that it is equivalent to the definition

$f(x) = Ax +f(0) $ for some $k\times d$ matrix $A$

Thank you!

share|improve this question

1 Answer 1

up vote 3 down vote accepted

$(\Longrightarrow)$ Suppose first that $f(\lambda x + (1-\lambda)y) = \lambda f(x) + (1-\lambda) f(y)$ for all $x, y \in \mathbb{R}^d$ and $\lambda \in \mathbb{R}$. Let $$g(x) = f(x) - f(0).$$ We have to show that $g$ is linear. This means that we have to check that

  • $g(cx) = cg(x)$ for all $x \in \mathbb{R}^d$ and $c \in \mathbb{R}$.

  • $g(x+y) = g(x) + g(y)$ for all $x, y\in \mathbb{R}^d$

For the first point, note that $$g(cx) = f(cx) - f(0)$$ by definition. Also, our hypothesis gives $f(cx) = cf(x) + (1-c)f(0)$ (by taking $\lambda = c$ and $y = 0$). You take it from here.

For the second point, note that $$g(x + y) = f(x+y) - f(0)$$ by definition. Also, our hypothesis gives $f(x+y) = \frac{1}{2}f(2x) + \frac{1}{2}f(2y)$ (why?) and that $f(2x) = 2f(x) - f(0)$ (why?). You take it from here.


$(\Longleftarrow)$ Suppose now that $f(x) = Ax + f(0)$ for some $k \times d$ matrix $A$. If $x,y \in \mathbb{R}^d$ and $\lambda \in \mathbb{R}$, then $$ \begin{align*} f(\lambda x + (1-\lambda)y) & = A(\lambda x + (1-\lambda)y) + f(0) \\ & = \ldots \\ & = \ldots \\ & = \lambda f(x) + (1-\lambda) f(y), \end{align*}$$ where the $\ldots$ means I've left the details for you to fill in.

share|improve this answer
    
This brings another question: How to show any linear mapping is of the form Ax for some matrix A? Thank you! –  Salih Ucan Feb 5 '13 at 9:50
2  
That's basic linear algebra. (Are you taking a linear algebra class?) Any matrix $A$ determines a linear map in the obvious way: that is, $h(x) = Ax$ is linear. Conversely, any linear map $h$ can be represented as a matrix by choosing bases for the domain and target. In particular, if $\{e_1, \ldots, e_d\}$ is a basis for the domain, then we can take $$A = [h(e_1) \cdots h(e_d) ]$$ as the matrix, where each $h(e_i) \in \mathbb{R}^k$ is written as a column. –  Jesse Madnick Feb 5 '13 at 9:54
    
Thank you Jesse! yes i am studying linear algebra now.. –  Salih Ucan Feb 5 '13 at 10:03

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.